Estimating the Size and Cost of the STD Prevention Services Safety Net. (November 2015) - Gift, Thomas L.; Haderxhanaj, Laura T.; Torrone, Elizabeth A.; Behl, Ajay S.; Romaguera, Raul A.; Leichliter, Jami S.
The Patient Protection and Affordable Care Act is expected to reduce the number of uninsured people in the United States during the next eight years, but more than 10% are expected to remain uninsured. Uninsured people are one of the main populations using publicly funded safety net sexually transmitted disease (STD) prevention services. Estimating the proportion of the uninsured population expected to need STD services could help identify the potential demand for safety net STD services and improve program planning. In 2013, an estimated 8.27 million people met the criteria for being in need of STD services. In 2023, 4.70 million uninsured people are expected to meet the criteria for being in need of STD services. As an example, the cost in 2014 U.S. dollars of providing chlamydia screening to these people was an estimated 271.1 million in 2013 and is estimated to be 153.8 million in 2023. A substantial need will continue to exist for safety net STD prevention services in coming years.